2022
DOI: 10.1007/s10654-022-00866-5
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the mortality rate for coronavirus disease 2019 compared to other causes of death: an analysis of population-wide data from 63 countries

Abstract: Men are more likely than women to die due to coronavirus disease 2019 (COVID-19). An open question is whether these sex differences reflect men’s generally poorer health and lower life expectancy compared to women of similar ages or if men face a unique COVID-19 disadvantage. Using age-specific data on COVID-19 mortality as well as cause-specific and all-cause mortality for 63 countries, we compared the sex difference in COVID-19 mortality to sex differences in all-cause mortality and mortality from other comm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
1
3
2
1
Order By: Relevance
“…A wide range of behavioral and biological factors have been proposed as plausible (non-mutually exclusive) explanations for the sex disparities in COVID-19 severity and outcomes, including sex differences in social, cultural, hygiene, and economic behaviors; differential prevalence of medical conditions associated with a higher risk of COVID-19 fatality, such as diabetes, hypertension, chronic cardiovascular disease, and respiratory disease; and effects of sex hormones on, for instance, virus entry and priming, as well as immune and inflammatory responses 31 , 33 . Nevertheless, it should be noted that the degree of sex differences in COVID-19 fatalities differed widely among countries 35 , 36 , and similar to the present study, some studies found no differential COVID-19 fatalities between sexes. For example, a study of an Italian cohort showed that death rates were not significantly different between males and females after adjusting for various confounding factors, including age and disease severity at hospital presentation 39 .…”
Section: Discussionsupporting
confidence: 86%
“…A wide range of behavioral and biological factors have been proposed as plausible (non-mutually exclusive) explanations for the sex disparities in COVID-19 severity and outcomes, including sex differences in social, cultural, hygiene, and economic behaviors; differential prevalence of medical conditions associated with a higher risk of COVID-19 fatality, such as diabetes, hypertension, chronic cardiovascular disease, and respiratory disease; and effects of sex hormones on, for instance, virus entry and priming, as well as immune and inflammatory responses 31 , 33 . Nevertheless, it should be noted that the degree of sex differences in COVID-19 fatalities differed widely among countries 35 , 36 , and similar to the present study, some studies found no differential COVID-19 fatalities between sexes. For example, a study of an Italian cohort showed that death rates were not significantly different between males and females after adjusting for various confounding factors, including age and disease severity at hospital presentation 39 .…”
Section: Discussionsupporting
confidence: 86%
“…Civil registration data in NFHS-5 subsample states that had high rates of pre-pandemic death registration for females and males (see Table S-1 for the states that meet this criteria) also showed larger increases in mortality between 2019 and 2020 for females compared to males in most states, as shown in Figure S-3. These patterns are in stark contrast to the global pattern of a greater increase in mortality during the COVID-19 pandemic for males compared to females (35,1,20). Such a large female disadvantage in the impact of the pandemic as observed in India has not been documented in any country.…”
Section: Resultscontrasting
confidence: 60%
“…Our findings demonstrate that the toll of the pandemic was experienced unevenly within India. Whereas in most countries, losses to life expectancy were greater for males than females (19,20), we document a loss in life expectancy among females that is one year more than for males. A larger mortality increase among females relative to males is also evident in India's vital statistics in subsample states that have high rates of male and female death registration.…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…Nuestras hipótesis apuntan a encontrar una disminución significativa de la e(0), con una diferencia mayor entre la e(0) esperada y observada para los hombres que respecto a las mujeres, dado que la evidencia internacional señala un mayor impacto directo del COVID-19 para esta subpoblación 11 , 12 , 13 . Además, esperamos encontrar impactos indirectos del COVID-19 en la mortalidad, causando variaciones significativas en otras causas de muerte, ya que han sido estudiados casos donde ciertas causas de muerte han disminuido producto de las restricciones de movilidad y otras medidas impuestas durante la pandemia 14 .…”
Section: Introductionunclassified